1989
DOI: 10.1083/jcb.109.4.1753
|View full text |Cite
|
Sign up to set email alerts
|

A novel 87,000-Mr protein associated with acetylcholine receptors in Torpedo electric organ and vertebrate skeletal muscle.

Abstract: Abstract. To identify proteins associated with nicotinic postsynaptic membranes, mAbs have been prepared to proteins extracted by alkaline pH or lithium diiodosalicylate from acetylcholine receptor-rich (AChR) membranes of Torpedo electric organ. Antibodies were obtained that recognized two novel proteins of 87,000 Mr and a 210,000:220,000 doublet as well as previously described proteins of 43,000 Mr, 58,000 (51,000 in our gel system), 270,000, and 37,000 (calelectrin). The 87-kD protein copurified with acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 43 publications
2
64
0
1
Order By: Relevance
“…6, was prepared by using Torpedo rapsyn as immunogen (16). Based upon epitope mapping studies it has been shown to recognize rapsyn amino acid sequence 396 -411.…”
Section: Expression Of Rapsyn Rapsyn Mutants and Nachr In 293t Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…6, was prepared by using Torpedo rapsyn as immunogen (16). Based upon epitope mapping studies it has been shown to recognize rapsyn amino acid sequence 396 -411.…”
Section: Expression Of Rapsyn Rapsyn Mutants and Nachr In 293t Cellsmentioning
confidence: 99%
“…The distribution of rapsyn domains fused to GFP was visualized by fluorescein isothiocyanate optics, while wild-type rapsyn was visualized by the binding of rhodamine-conjugated goat anti-mouse antibody to mAb 19F4A, a mouse monoclonal that recognizes rapsyn of many species (16). Based upon epitope mapping studies with Torpedo rapsyn, mAb194A recognizes a COOH-terminal epitope (rapsyn-(396 -411)), 3 and based upon immunofluorescence it did not recognize rapsyn-(1-360) or other smaller fragments expressed in 293T cells (data not shown).…”
Section: Rapsyn Coiled-coil Domain Is Essential For Clustering Nachrsmentioning
confidence: 99%
“…Two other dystrophin-related proteins, utrophin and the 87K protein, are products of different genes. The 87K protein, a substrate for tyrosine phosphorylation, was first discovered as a postsynaptic protein of Torpedo electric organ [13]. The 87K protein shows modest but significant homology to the CRCT region of dystrophin [14].…”
Section: Introductionmentioning
confidence: 99%
“…The Torpedo 87K protein was first identified as a protein closely associated with the acetylcholine receptor [28], and then found to associate with Torpedo syntrophin (58K protein) [26,29]. Recently, the 87K protein was reported as a dystrophin homologue, since it was homologous to the cysteine-rich and C-terminal domains of dystrophin with an overall 27% amino acid identity over 546 amino acids [26].…”
Section: Discussionmentioning
confidence: 99%